Comments on "Fifty Years of Distortions in World Food Markets" - Díaz-Bonilla, Eugenio (2009)
Eugenio Diaz Bonilla, Executive Director for Argentina and Haiti, Inter-American Development Bank 14th October 2008, International Food Policy Research Institute, Washington D.C.